INTRODUCTION TO BASIC ARABIC LANGUAGE FOR COMMUNITIES IN AIR TEMAM DISTRICT, LUBUKLINGGAU CITY - Umam, Hapizil (Lembaga Penelitian, Publikasi Ilmiah dan Pengabdian kepada Masyarakat (LP3M), 2024)
Indonesia is the country with the largest Muslim majority in the world, so learning Arabic is a must. Good knowledge of Arabic can help deepen and study Islamic religious knowledge. This service activity was carried out at the Darul Hidayah Madani (DHM) Islamic Boarding School, Lubuklinggau City, which involved the people of Air Temam sub-district, Lubuklinggau City for 11 days and was attended by 20 people. The form of activity is carried out through presentation and introduction of basic Arabic language material. This activity aims to introduce the basics of Arabic to the people of Air Temam Village, Lubuklinggau City as a strengthening in understanding the Koran. The methods used in implementing this program are descriptive narrative, memorization and question and answer. The results of this activity. This basic introduction to Arabic language program has provided positive results for the community in the Air Temam sub-district. The Air Temam community's knowledge of Arabic vocabulary before participating in this activity was still small and weak, after participating in this activity their vocabulary knowledge increased gradually.